2016
DOI: 10.1016/j.aanat.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the anatomical knowledge of laypersons and their attitudes towards the clinical importance of gross anatomy in medicine

Abstract: If it is accepted that increasingly we live within a consumerist society then axiomatically 'ownership' of medical training does not belong to political authorities (whether governmental or medical), nor to the medical profession, nor indeed to the teachers, educationalists and even the students but to the laypersons in society who are patients or potential patients (viz. the clients/recipients of medical care). As yet, however, there has been no attempt to evaluate how much anatomy laypersons know and what th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…While 130 hr may seem a significant amount of time, in the context of the entire medical course, this corresponds merely with 3 full weeks of anatomy tuition in a year or 2% of the entire course. These changes are occurring despite anatomists, medical students and laypersons opining that gross anatomy is crucial and fundamental for medical education and training (e.g., Patel and Moxham, , ; Moxham and Plaisant, ; Moxham and Moxham, ; Pabst, ; Kerby et al, ; Moxham et al, ). Globally, the range and variety of medical curricula have changed markedly from the traditional model of 2 or 3 years “preclinical studies” followed by 2 or 3 years of “clinical studies” to systems‐based integrated curricula.…”
Section: Introductionmentioning
confidence: 99%
“…While 130 hr may seem a significant amount of time, in the context of the entire medical course, this corresponds merely with 3 full weeks of anatomy tuition in a year or 2% of the entire course. These changes are occurring despite anatomists, medical students and laypersons opining that gross anatomy is crucial and fundamental for medical education and training (e.g., Patel and Moxham, , ; Moxham and Plaisant, ; Moxham and Moxham, ; Pabst, ; Kerby et al, ; Moxham et al, ). Globally, the range and variety of medical curricula have changed markedly from the traditional model of 2 or 3 years “preclinical studies” followed by 2 or 3 years of “clinical studies” to systems‐based integrated curricula.…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, we live in a consumerist world where the consumer expects to have an input into matters that concern them (and what can be more concerning than healthcare). Recently, we published a article where we surveyed the opinions of laypersons in the UK and France about their attitudes toward the importance of the anatomical sciences (Moxham et al, 2016). We found that the laypersons (i.e., patients or future patients) had an unexpectedly high knowledge of anatomy and we also discovered that they expressed very strong views about the relevance of anatomy and of the importance of students studying anatomy using cadavers.…”
Section: Dear Editormentioning
confidence: 96%
“…In this respect, laypersons in the U.K. and in France (i.e., the consumers of healthcare) were in favor of high levels of training in anatomy. Additionally, they evinced a critical loss of esteem for the medical profession when made aware that students no longer dissected (Moxham et al, 2016). I very much hope that, when it comes to advocating the importance of our discipline, my suspicions that anatomists are too often their own worst enemy prove to be unfounded.…”
Section: To the Editor Clinical Anatomymentioning
confidence: 99%